Il progetto EDUFARM. Connubio tra Università e fattorie didattiche - Giuseppe De Simone; Anna Cuozzo; Alessandra Gargano; Nadia Carlomagno (Firenze University Press, 2017)
The theory of action and enactivism make possible to get back the attention on doing, on body and on thinking, beloved to the activist tradition. Especially, the lab didactics has its roots in New Education, which is at the bottom of pedagogi-cal activism that sees a revolution in the educational relationship in the puerocentric paradigm, in which the child becomes the active protagonist of the educational process and not a simple adult action's passive receiver. Towards, the didactic farm is redefining its role in the educational system to lead to the devel-opment of didactic laboratory in educational practice. The educational value of this pedagogical place can be traced back to three main ideas: the active pedagogy of learning by doing; direct contact with animals and plants in their natural envi-ronment: it allows visitors to acquire knowledge and skills that cannot be learned in urban context; the sensory stimulation of a rich environment that makes the child protagonist of their knowledge. With the Edufarm research project we want-ed to build a laboratory course with didactic farm as setting and learning by doing as the whole project's "red thread".